Education in political activity of the JMO deputies in the National Assembly of the Kingdom of Serbs, Croats and Slovenes - Selimović, Sead (Historical Thought, 2025)
The Yugoslav Muslim Organization was the largest political party in Bosnia and Herzegovina during the Kingdom of Serbs, Croats and Slovenes. The deputies of this party were very active in the National Assembly of the Kingdom of Serbs, Croats and Slovenes. They often pointed out the problems of education in Bosnia and Herzegovina.